Pathological and parasitological investigations in an adult bottlenose dolphin (tursiops truncatus) - Sümbül Serap BİRİNCİOĞLU; Süleyman AYPAK; Hamdi AVCI; Birol BİRİNCİOĞLU; Emrah İPEK; Ayşe Nur AKKOÇ (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2017)
This case aimed to perform pathological and parasitological examinations on an adult male bottlenose dolphin (Tursiops truncatus), which was found dead on the coast of Aegean Sea (Kusadasi/Davutlar/Aydin-Turkey). At necropsy, intestinal volvulus and fibrinopurulent peritonitis were observed. In the histopathologic examination, severe vascular changes including oedema and hemorrhages were observed in the intestines formed by volvulus and peritoneum. In the parasitological examination revealed some ectoparasites (Copepoda: Pennellidae) on the skin. Also, Stenurus minor (S. minor) was detected in the lungs. In conclusion, severe ectoparasite infestation, intestinal volvulus, S. minor in the lungs, and severe renal calcinosis were defined in the adult bottlenose dolphin.